Whose Classical Music? Reflections on Film Adaptation - Kramer, Lawrence (Journal of Film Music, 2009)
Two seemingly unrelated things caught my attention as I mulled over the topic of this essay. They were a fragment of Chopin in a just-released Hollywood romance and a densely argued patch of German art-historical theorizing from the 1920s. By some strange catalytic logic, the two did form a relationship for me—even, I would like to think, a revealing one. You be the judge. My own interest is in music, not art history, and it has lately seemed important to me to think about how the use of preexisting music in film, especially classical music, helps shape cinematic meaning.It’s a question that takes on a special edge today, as classical music continues to be used in many films despite the widespread sense that it has suffered a decline in cultural authority, especially in the United States